The Role of Village-Owned Enterprises in Improving the Economy of the Nglurup Village Community, Sendang District, Tulungagung Regency - Raditya Prima Widiatmaka; Sri Wibawani (Universitas Medan Area, 2022)
This article aims to describe the role of the Sri Rejeki Village Owned Enterprise in improving the economy of the Nglurup Village community. The problem is focused on the role of the Sri Rejeki Village Owned Enterprise in improving the community's economy. To approach this problem, the reference used to describe the role of Village-Owned Enterprises is Mardikanto's theory regarding the achievement of community empowerment goals, namely institutional improvement, business improvement, and income improvement. Primary data was obtained through interviews while secondary data was obtained through observation, documentation, articles, literature, and journals and then analyzed qualitatively. The results of this study, Sri Rejeki Village Owned Enterprises in improving the community's economy has played a fairly good role with institutional improvements, business improvements, and income improvements carried out in Sri Rejeki Enterprises. This study concludes that the role of the Sri Rejeki Village-Owned Enterprises in improving the community's economy is currently playing a fairly good role even though there are obstacles such as budget cuts due to the Covid-19 Pandemic, causing some plans to not be implemented.